Influence of Cu Substitution on the Properties of Hydroxyapatite Targets and Deposited Coatings; Coatings; Vol. 13, iss. 11 - Prosolov K. A. Konstantin Aleksandrovich; Lastovka V. V. Vladimir Viktorovich; Khimich M. A. Margarita Andreevna; Glukhov I. A. Ivan Aleksandrovich; Kashin A. D. Aleksandr Daniilovich; Luginin N. A. Nikita Andreevich; Sharkeev Yu. P. Yury Petrovich (2023, 2023)
In addressing the issue of optimizing the mechanical and electrochemical properties of hydroxyapatite (CaP) materials for biomedical applications, this research explored the incorporation of copper (Cu) into the material and scrutinized its impact through various processing stages, from powders to ceramics and finally to coatings. Our investigation indicated that the integration of CuO into CaP significantly changed the lattice parameters of hydroxyapatite from manufactured powders to sintered targets, indicating a structural evolution. Simultaneously, the change in the elemental composition and Ca/P ratio was also followed by each step from manufactured powders to deposited coatings. Mechanical testing revealed an impressive increase in the hardness of coatings to a high of 37 GPa for the 0.2CuO-CaP sample, a substantial improvement when compared to 13 GPa for pure Ti. The corrosion resistance of the coatings also improved, evidenced by the decrease in corrosion current density (Icorr) from 60.2 ± 5.2 nA/cm2 for pure Ti to a lower 3.9 ± 0.5 nA/cm2 for the CaP coating. Our study has revealed that the structural, mechanical, and electrochemical properties of CaP materials can be finely adjusted through the addition of Cu, promising advances in the realm of biomedical applications. Moreover, these results hint at the potential to tune the electrophysical characteristics of CaP coatings, an avenue for future exploration